Efektivitas Pembinaan dan Pengawasan Keuangan Desa oleh Kecamatan Parang Kabupaten Magetan - Rahmawati, Nita; Ratih Wulandari, Florentina; Kismartini, Kismartini (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2025)
This study is motivated by the unmet targets of village financial administration management in Parang District. It aims to analyze the effectiveness of coaching and supervision, as well as the factors influencing village government financial administration. The research employs a descriptive qualitative approach. Data were collected through interviews, observations, and documentation involving 11 informants, and analyzed using an interactive qualitative data analysis model with triangulation to ensure data validity. The findings show that coaching in village financial administration has clear objectives, actors, and materials; however, its implementation has not been optimal due to limited apparatus capacity, the absence of measurable performance targets, and the lack of standardized SOPs and technical guidelines. Supervision has been conducted systematically through monitoring, examination, guidance, and corrective actions, yet it requires further strengthening of sub-district apparatus capacity to ensure effectiveness and sustainability. Factors contributing to suboptimal financial administration include environmental changes, administrative complexity, technical errors, delegated authority, and leadership issues.The study concludes that village financial administration management still faces significant challenges related to implementation standards, apparatus capacity, and inter-agency coordination. Therefore, it is recommended to develop standardized SOPs and technical guidelines, enhance apparatus capacity through continuous technical training, and strengthen coordination among coaches, supervisors, and village officials to improve the accountability of village financial management.